PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN AL-QUR’AN HADITS SISWA KELAS X SMK MUHAMMADIYAH 2 KARANGANYAR TAHUN PELAJARAN 2025/2026 - Adli Nashih Setya Kusuma; Joko Subando (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Purpose: This study examines the influence of learning motivation on learning outcomes in the Qur'an Hadith subject among 10th-grade students at SMK Muhammadiyah 2 Karanganyar in the 2025/2026 academic year. Method: A quantitative correlational approach was employed. The sample comprised 35 tenth-grade students. The main instruments were a learning motivation questionnaire and academic records for the Qur'an Hadith subject. Data were analyzed using descriptive statistics and Pearson correlation tests. Results: Overall student motivation level was moderate to high, with 80.0% of students falling in the medium-to-high motivation category. Learning outcomes were fairly good as well, with 68.5% of students achieving medium-to-high outcome categories. Correlation analysis showed a strong positive relationship between learning motivation and outcomes (r = 0.789, p < 0.01). Motivation explained about 62.3% of the variance in learning outcomes, indicating that learning motivation significantly influences achievement in Qur'an Hadith. Conclusion: The higher the students’ learning motivation, the better their learning outcomes. The findings imply that efforts to boost motivation – for example, through innovative teaching strategies, humanistic approaches, and reinforcement of Islamic values – can improve student performance in the Qur'an Hadith subject.